"Encountering (China, My) Sorrow". Issue 1 (1st September 1998) - Fong Young, Suzie Sau
The Buddhists say that all life is sorrow, but Dai Sijie's China My Sorrow (1989), while borrowing freely from the 2000-year-old tradition of Buddhist thought, does not ignore the role of the "politics of everyday resentment" in making human life narrower, excessively violent, and irreconciliable to the best theories of high culture.